OR2AT4 and OR1A2 counterregulate molecular pathophysiological processes of steroid-resistant inflammatory lung diseases in human alveolar macrophages - Daniel Weidinger; Kaschin Jamal Jameel; Desiree Alisch; Julian Jacobsen; Paul Bürger; Matthias Ruhe; Faisal Yusuf; Simon Rohde; Klemens Störtkuhl; Peter Kaufmann; Juliane Kronsbein; Marcus Peters; et al. (BMC, 2022)
Abstract Background Therapeutic options for steroid-resistant non-type 2 inflammation in obstructive lung diseases are lacking. Alveolar macrophages are central in the progression of these diseases by releasing proinflammatory cytokines, making them promising targets for new therapeutic approaches. Extra nasal expressed olfactory receptors (ORs) mediate various cellular processes, but clinical data are lacking. This work investigates whether ORs in human primary alveolar macrophages could impact pathophysiological processes and could be considered as therapeutic targets. Methods Human primary alveolar macrophages were isolated from bronchoalveolar lavages of 50 patients with pulmonary diseases. The expression of ORs was validated using RT-PCR, immunocytochemical staining, and Western blot. Changes in intracellular calcium levels were analyzed in real-time by calcium imaging. A luminescent assay was used to measure the cAMP concentration after OR stimulation. Cytokine secretion was measured in cell supernatants 24 h after stimulation by ELISA. Phagocytic ability was measured by the uptake of fluorescent-labeled beads by flow cytometry. Results We demonstrated the expression of functional OR2AT4 and OR1A2 on mRNA and protein levels. Both ORs were primarily located in the plasma membrane. Stimulation with Sandalore, the ligand of OR2AT4, and Citronellal, the ligand of OR1A2, triggered a transient increase of intracellular calcium and cAMP. In the case of Sandalore, this calcium increase was based on a cAMP-dependent signaling pathway. Stimulation of alveolar macrophages with Sandalore and Citronellal reduced phagocytic capacity and release of proinflammatory cytokines. Conclusion These are the first indications for utilizing olfactory receptors as therapeutic target molecules in treating steroid-resistant lung diseases with non-type 2 inflammation.